Suitable technology for a household scale workshop systems for the treatment of wastewater - Azwarudin Azwarudin; Hijriati Sholehah; Diano Karno; Muhamad Majdi (Jurnal Pijar Mipa, 2023)
One of the causes of water pollution is the presence of workshop activities. Gasoline residue from washing spare parts and washing hands after repairing and maintaining motor vehicles can harm the surrounding environment, namely water pollution. This study aims to determine the efficiency of reducing the levels of pH, BOD, COD, TSS, oil and grease, Ammonia, and total coliform in wastewater from Astra workshop operations using three treatment and treatment units in the piping section and to determine the design of wastewater treatment tanks for operation astra workshop. Based on the preliminary test results, the waste from Astra workshop activities had a pH content of 7.2, a BOD content of 2.9 mg/l, a COD content of 58 mg/l, a TSS content of 2.45 mg/l, an oil and fat content of 8.702 mg/l, the ammonia content was 0.027 mg/l. The total coliform content was 2000 MPN/ml. Of these values, there is one parameter that does not meet the quality standards according to the Decree of the Minister of Environment and Forestry No. 68 of  2016 concerning Domestic Waste Quality Standards, namely a pH concentration of 6-9, a maximum level of BOD of 30 mg/l, a maximum level of COD of 100 mg/l, a maximum level of TSS of 30 mg/l, a maximum concentration of oils and fats allowed 5 mg/l, maximum ammonia concentration of 10 mg/l, and maximum permitted total coliform content of 3000 MPN/ml. This workshop liquid waste treatment uses three treatment and treatment units in the piping section with one filtration media, which is carried out in duplicate to anticipate and minimize the possibility of errors that can occur during the process. Efficiency in reducing parameters in liquid waste from Astra workshop operations using filtration media and treatment in the piping section can reduce the pH concentration by -15.29%, from an initial concentration of 7.2 to 8.5, TSS by 59.18% from an initial concentration of 2.45 mg/l to 1 mg /l. BOD was 72.41% from an initial concentration of 2.9 mg/l to 0.8 mg/l. COD was 65.51% from an initial concentration of 58 mg/l to 20 mg/l. Fatty oil was 45.41% from an initial concentration of 8,702 mg/l to 4.75 mg/l. Ammonia by 48.14% from the initial concentration of 0.027 mg/l to 0.014 mg/l, and Total Coliform by 100% from 2000 MPN/ml to 0 MPN/ml.